The localization development path of Chinese R&B music: A study based on representative works of David Tao and Jay Chou - Ruoyuan Jing; Jinky Jane C. Simeon (Human Resource Management Academic Research Society, 2024)
The development of contemporary Chinese R&B music has undergone a complex process from initial introduction in Hong Kong and Taiwan regions to localized integration. However, existing research mostly focuses on macro-level descriptions, and even when specific works and artists are discussed, they often lack systematic depth. This paper adopts a combination of literature review and case study methodologies. Firstly, it systematically reviews the introduction, early development, and localization characteristics of R&B music in China, pointing out the shortcomings of current research. Subsequently, it selects four representative works by David Tao and Jay Chou as cases to deeply analyze the specific manifestations of Chinese R&B music in musical characteristics, cultural fusion, and vocal techniques. The study finds that these two artists have played a key role in the localization process of R&B music in China. Their innovative practices have enriched the diversity of Chinese pop music, created a unique "Chinese style" R&B, and promoted the localization process of R&B music in China. Based on the analysis, the study also proposes relevant strategies and suggestions to promote the healthy and sustainable development of Chinese R&B music, providing new perspectives for further understanding the development path and future trends of Chinese R&B music.